Melanocortin-4 Receptor in Spotted Sea Bass, Lateolabrax maculatus: Cloning, Tissue Distribution, Physiology, and Pharmacology - Zhang, Kai-Qiang; Hou, Zhi-Shuai; Wen, Hai-Shen; Li, Yun; Qi, Xin; Li, Wen-Juan; Tao, Ya-Xiong (Frontiers in Endocrinology, 2019)
Melanocortin-4 receptor (MC4R) plays important roles in regulation of multiple physiological processes including energy homeostasis, reproduction, sexual function, and other functions in mammals. Recent studies suggested that teleost MC4Rs have different physiological functions and pharmacological characteristics when compared to mammalian MC4Rs. In this study, we investigated spotted sea bass (Lateolabrax maculatus) MC4R (LmMC4R) physiology and pharmacology. Spotted sea bass mc4r consisted of a 984 bp open reading frame encoding a protein of 327 amino acids. LmMC4R was homologous to those of several teleost MC4Rs and human MC4R (hMC4R). qRT-PCR and in situ hybridization revealed that mc4r transcripts were highly expressed in the brain, followed by pituitary and liver. Brain mc4r transcripts were down-regulated in long-term and short-term fasting challenges. LmMC4R was a functional receptor with lower maximal binding and higher basal activity than hMC4R. THIQ was not able to displace 125I-NDP-MSH but could affect intracellular cAMP accumulation, suggesting that it was an allosteric ligand for LmMC4R. In vitro studies with spotted sea bass brain cells indicated that mRNA levels of neuropeptide Y and Agouti-related peptide were down-regulated by α-MSH. In summary, we cloned spotted sea bass MC4R, and showed that it had different pharmacological properties compared to hMC4R, and potentially different functions.